(untitled) (Netherlands, 1997)
Contents: Overview of workshop and budget results; budgets for Mexican coastal lagoons; conclusions and implications for lagoon comparison.
Keywords: Coastal ecology,Climatic changes,Sinh thái học ven biển,Thay đổi khí hậu; Research,International cooperation,Nghiên cứu,Hợp tác quốc tế